Emotional Intelligence and Mathematical Resilience of Pre-service Teachers - Fabregas, Shena R.; Tamayo, April Rose R.; Villanueva, Kristine Jane E.; Aguila, Jenny Rose S. (Community and Social Development Journal, 2025)
The study investigated the relationship between emotional intelligence and mathematical resilience in pre-service teachers using descriptive-correlational quantitative research. The researchers used self-report questionnaires to collect data from 88 pre-service teachers at Batangas State University JPLPC-Malvar’s College of Teacher Education Major in Mathematics. The questionnaires contained items that assessed EI as well as mathematical resilience. The study’s findings indicate a positive relationship between EI and mathematical resilience. Pre-service teachers with higher EI scores were more likely to be resilient in mathematics, implying that higher levels of emotional intelligence can contribute to better performance. Pre-service teachers with higher levels of emotional intelligence were more likely to be resilient in mathematics, implying that higher levels of emotional intelligence can contribute to better outcomes in mathematical learning. Overall, the research emphasizes the significance of emotional intelligence in awareness of mathematical resilience among pre-service teachers. To improve mathematical resilience, pre-service teacher training programs should focus on developing emotional intelligence and promoting a positive attitude towards mathematics, according to the findings.